Metal matrix composite products by vibration casting method - Sayuti, M.; Sulaiman, Shamsuddin; Baharudin, B. T. Hang Tuah; Mohd Ariffin, Mohd Khairol Anuar (Elsevier, 2016)
Metal matrix composites are engineered materials which are a combination of two or more materials, one of which is a metal, whose tailored properties can be attained by systematic combination of different constituents. In this study, titanium carbide particulate reinforced aluminiums 11,8 wt% silicon alloy matrix composites were fabricated by carbon dioxide sand moulding process by varying the particulate addition by weight fraction on percentage basis using mechanical vibration mould. The influence of a wide range of vibration amplitudes and frequencies on the solidification kinetics, microstructure formation and mechanical properties of Titanium carbide reinforced aluminiums 11,8 wt% silicon alloy were examined. Results show strong influence of mould vibration during solidification on the fabricated composites. The mechanical properties such as tensile strength, impact strength, surface hardness and physical properties such as density, thermal conductivity were significantly increased as a result of mould vibration. The maximum tensile strength is 141.125 MPa with vibration and 135.832 MPa without vibration. The maximum impact energy is 15.073 kJ with vibration and 14.514 kJ without vibration and hardness value based Rockwell superficial 15N-S scale is 85.88 for 2% without vibration and 86.08 with vibration. In addition, the change in microstructure and mechanical properties were successfully represented by the changes in solidification characteristics. Various vibration frequencies has reduced the lamellar spacing that changes the microstructure of the composites which as a result became more fibrous. The corresponding changes in mechanical properties indicate that ductility is more influenced by vibration than without vibration. The increase in ductility was believed to be due to the structural refinement.